2013
DOI: 10.1007/978-3-642-38067-9_16
|View full text |Cite
|
Sign up to set email alerts
|

Selective Clustering Ensemble Based on Covariance

Abstract: Abstract. Clustering Ensemble effectively improves clustering accuracy, stability and robustness, which is most resulted from the diversity of the base clustering results. It is a key point to measure the diversity of clustering results. This paper proposes a method to measure diversity of base clustering results and a covariance-based selective clustering ensemble algorithm. Experiments on 20 UCI data sets show that this algorithm effectively improves the clustering performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A more e cient consensus solution can be obtained if the ensemble members are different from each other (diversity) and have satisfactory quality. [40,62] Especially when the ensemble size is small, combining identical clustering solutions leads to an inaccurate consensus solution. [32] In the supervised classi cation task, the classi ers are ranked based on their individual performance on a held-out test set, and the best ones are picked.…”
Section: Related Workmentioning
confidence: 99%
“…A more e cient consensus solution can be obtained if the ensemble members are different from each other (diversity) and have satisfactory quality. [40,62] Especially when the ensemble size is small, combining identical clustering solutions leads to an inaccurate consensus solution. [32] In the supervised classi cation task, the classi ers are ranked based on their individual performance on a held-out test set, and the best ones are picked.…”
Section: Related Workmentioning
confidence: 99%
“…The main problem in the clustering ensemble selection is how to evaluate each cluster. The literature consists of different quality and diversity measures implemented to ensemble members [21,22]. The basis of these measures is the match index between the two partitions.…”
Section: Related Workmentioning
confidence: 99%
“…In another study, Hadjitodorov et al [14] used the ARI diversity measure to select ensemble members. Lu et al [21] suggested a diversity criterion based on covariance. Alizadeh et al [26] proposed a CES method in which clusters were selected based on diversity and quality measures.…”
Section: Related Workmentioning
confidence: 99%